2014
DOI: 10.4330/wjc.v6.i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Is diabetic cardiomyopathy a specific entity?

Abstract: Diabetes mellitus (DM) is characterised by hyperglycemia, insulin resistance and metabolic dysregulation leading to diastolic and systolic dysfunction in diabetes. In this review, the pathogenetic and pathomorphological changes leading to diastolic and systolic dysfunction in diabetes are discussed. Changes in metabolic signalling pathways, mediators and effectors contribute to the pathogenesis of cardiac dysfunction in DM called diabetic cardiomyopathy (DC). Echocardiographic studies report on the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…Although experimental ( 19 , 20 , 21 ) and clinical ( 22 , 23 , 24 ) evidence is growing, the existence of a specific diabetic cardiomyopathy is still a matter of debate in this population ( 4 , 25 ). The majority of previous studies ( 10 , 13 , 26 ) involved type 2 diabetic patients, with coexistence of hypertension (38–64%), hypercholesterolemia and obesity, relatively advanced mean age (up to 60 years) and a short diabetes duration (less than 10 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although experimental ( 19 , 20 , 21 ) and clinical ( 22 , 23 , 24 ) evidence is growing, the existence of a specific diabetic cardiomyopathy is still a matter of debate in this population ( 4 , 25 ). The majority of previous studies ( 10 , 13 , 26 ) involved type 2 diabetic patients, with coexistence of hypertension (38–64%), hypercholesterolemia and obesity, relatively advanced mean age (up to 60 years) and a short diabetes duration (less than 10 years).…”
Section: Discussionmentioning
confidence: 99%
“…Whether diastolic function highlights an early stage of diabetic cardiomyopathy before progressing to more significant systolic dysfunction has been controversial ( 5 , 25 ). The prevalence ranges from 23 to 75% depending on the methods used and populations studied (46% in a study based on the current guidelines) ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent clinical and epidemiological studies have confirmed these observations [4,5], suggesting that diabetes can damage the cardiac tissue independently of other cardiovascular risk factors. Such associations have provided a credible existence of DCM as a unique clinical entity, independent of hypertension, CAD, left ventricular hypertrophy (LVH), atrial fibrillation, or any other known cardiac diseases, leading to HF, caused by complex relationships between metabolic abnormalities that accompany diabetes and its cellular consequences [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, insulin resistance and an increase in the mitochondrial in ux of fatty acids predispose to an overproduction of superoxide ions involved in the genesis of hypertrophy, brosis, and left ventricular dysfunction. Furthermore, IR generates reactive oxygen species which are involved in the genesis of LVH and brosis [67].…”
Section: Discussionmentioning
confidence: 99%